Respuesta :

Answer:

3(x + 2)(2x - 5)

Step-by-step explanation:

Given

6x² - 3x - 30 ← factor out 3 from each term

= 3(2x² - x - 10) ← factor the quadratic

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 2 × - 10 = - 20 and sum = - 1

The factors are + 4 and - 5

Use these factors to split the x- term

2x² + 4x - 5x - 10 ( factor the first/second and third/fourth terms )

= 2x(x + 2) - 5(x + 2) ← factor out (x + 2) from each term

= (x + 2)(2x - 5), thus

2x² - x - 10 = (x + 2)(2x - 5) and

6x² - 3x - 30

= 3(x + 2)(2x - 5) ← in factored form